In vitro selection of mutant HDM2 resistant to nutlin inhibition - Wei, Siau Jia. (2014)
HDM2 binds to the p53 tumour suppressor and targets it for proteosomal degradation. Presently in clinical trials, the small molecule Nutlin-3A competitively binds to HDM2 and abrogates its repressive function. Using a novel in vitro selection methodology, we simulated the emergence of resistance by evolving HDM2 mutants capable of binding p53 in the presence of Nutlin concentrations that inhibit the wild-type HDM2-p53 interaction. The in vitro phenotypes were recapitulated in ex vivo assays measuring both p53 transactivation function and the direct p53-HDM2 interaction in the presence of Nutlin. Mutations conferring drug resistance were not confined to the N-terminal p53/Nutlin–binding domain, and were additionally seen in the acidic, zinc finger and RING domains. Mechanistic insights gleaned from this broad spectrum of mutations will aid in future drug design and further our understanding of the complex p53-HDM2 interaction.